2017
DOI: 10.1016/j.joca.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage cell-based cartilage repair in a rabbit model: cell tracking and in vivo chondrogenesis of human umbilical cord blood-derived mesenchymal stem cells and hyaluronic acid hydrogel composite

Abstract: Transplanting hUCB-MSCs and HA composite promote cartilage repair and interactions between hUCB-MSCs and host cells initiated by paracrine action may play an important role in cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…The process of stem cell isolation and cultivation is easier in comparison to primary chondrocytes or osteoblasts [38,39]. The osteogenic and chondrogenic differentiation potential of MSCs in conjunction with the engrafting ability are crucial for cartilage [17,40,41] and bone regeneration in vivo [42]. Current literature describes examples of the beneficial effects of blood product supplementation on adi-pogenic [43], chondrogenic [44][45][46], and osteogenic differentiation of MSCs [45,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of stem cell isolation and cultivation is easier in comparison to primary chondrocytes or osteoblasts [38,39]. The osteogenic and chondrogenic differentiation potential of MSCs in conjunction with the engrafting ability are crucial for cartilage [17,40,41] and bone regeneration in vivo [42]. Current literature describes examples of the beneficial effects of blood product supplementation on adi-pogenic [43], chondrogenic [44][45][46], and osteogenic differentiation of MSCs [45,47].…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH was used as a housekeeping gene. PCR conditions were optimized for annealing temperature and limited cycle number (40) to ensure that product formation was in the responsive range.…”
Section: Metabolic Activity Assay (Xtt Assay)mentioning
confidence: 99%
“…28 Satué et al 28 demonstrated the safety and efficacy of IA-injected MSCs in the knee and stated that MSCs remained in the synovial cavity, engrafted within the cartilage lesion, and were detectable up to 1 month postinjection; no adverse effects after injection were observed. 28 Other authors also confirmed the presence of MSCs in the knee joint at 3 months, 29 8 weeks, 30 and 14 days after implantation. 31 Numerous studies have reported that the intravenous infusion or intra-articular transplantation of various types of MSCs improves arthritic symptoms in animal models by paracrine mechanisms.…”
Section: Introductionmentioning
confidence: 71%
“…Previous cell tracking results after intra-articular cell transplantation show gradual decrease of transplanted cells over time 29,30 . A cartilage repair study utilizing human umbilical cord blood-derived MSC-hyaluronic acid gel composite in a rabbit model resulted in disappearance of human origin cells by the 16 th wk 31 . One of the strengths of this study is the demonstration of the TEC's continued presence and differentiation after in vivo www.nature.com/scientificreports www.nature.com/scientificreports/ transplantation, as shown in our remodeling and cell distribution data, Time-dependent cartilage differentiation ( Fig.…”
Section: Discussionmentioning
confidence: 99%